Turnover Intention in the Hotel Industry: The Employees' Perceptions - Nurul Sukma Lestari; Veithzal Rivai Zainal; Syafrizal Chan; Lenny Christina Nawangsari (Universitas Ahmad Dahlan, 2023)
The hotel industry is rapidly expanding, needing more employees. The high demand for employees may lead to tighter competition in the job market, increasing employee turnover. This study aims to provide statistical evidence about the role of job stress, job insecurity, and compensation in explaining turnover intention among hotel employees. Primary data related to hotel employees' perceptions were collected using an online survey. The survey involved 135 employees of Jakarta's five-star hotels. The data were analyzed using Partial Least Square Structural Equation Modelling (PLS-SEM) to test three research hypotheses. The analysis results show that job stress and job insecurity positively relate to turnover intention in the hotel industry, whereas compensation is negatively associated with turnover intention. The finding could provide insight for hotel managers on reducing employee turnover. It also contributes to the upward literature on the hospitality and tourism industry.